Clinical outcomes of routine opt‐out antenatal human immunodeficiency virus screening: a systematic review. Issue 3 (17th August 2016) - Ibekwe, Everistus; Haigh, Carol; Duncan, Fiona; Fatoye, Francis
Abstract : Aims and objectives: To evaluate the clinical outcome of routine screening of human immunodeficiency virus in antenatal clinic settings. Background: Despite the growing advances in human immunodeficiency virus management, nearly 30% of the estimated 1·5 million seropositive pregnant women are undiagnosed. Routine opt‐out testing is a strategy endorsed by the World Health Organization in2007 to increase testing rates in clinical settings. Design: A systematic review of relevant published literature. Methods: A comprehensive electronic search for relevant studies in Science Direct, MEDLINE, SCOPUS, CINAHL and PubMed was conducted with search terms (Box 2). Hand searches were also conducted for additional resources. There were no geographical restrictions. Searches were restricted to English language and studies conducted between 1998–2015; totaling 1097 were retrieved and carefully appraised for review. Eighteen studies were eligible for review: eight from Africa, five from the United States, three from Europe, one from Australia and one from Asia. Results: Fourteen studies reported increases in human immunodeficiency virus testing rate. Following the introduction of routine testing, human immunodeficiency virus testing rates increased from values ranging from 68–99·9% with median value of 88%. The comparison studies reported testing uptake of 22–93·5% with median value of 59%. Maternal human immunodeficiency virus case detection rates nearly doubled following adoption of routine testing at values of 99 and 45% during opt‐in. Linkage to treatment and care for prevention of vertical transmission was reported on six studies, and results ranged between 12·9–77·2%. Conclusion: The findings show that irrespective of human immunodeficiency virus epidemiological scenarios, routine testing gave more women opportunity to learn their human immunodeficiency virus status and take measures for prevention of mother‐to‐child transmission of human immunodeficiency virus. Future studies should focus on identifying strategies to improving linkages to treatment and care for prevention of vertical transmission. Relevance to clinical practice: Understanding the contributions of Routine opt‐out testing in antenatal clinic would help practitioners adopt the novel testing model for more mothers to learn their human immunodeficiency virus status for prevention of mother‐to‐child transmission.